2017
DOI: 10.1634/theoncologist.2017-0186
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study with Lead-In Safety Cohort of 5-Fluorouracil, Oxaliplatin, and Lapatinib in Combination with Radiation Therapy as Neoadjuvant Treatment for Patients with Localized HER2-Positive Esophagogastric Adenocarcinomas

Abstract: Lessons Learned.Neoadjuvant 5‐fluorouracil, oxaliplatin, and lapatinib in combination with radiation therapy is safe for neoadjuvant treatment for patients with localized human epidermal growth receptor 2‐positive esophagogastric adenocarcinoma.Evaluation of this drug combination in a larger patient pool would allow for more accurate analysis of its efficacy. Background.The optimal design of neoadjuvant chemoradiation for the treatment of localized esophagogastric cancers is the subject of much debate. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“… 42 Lapatinib is widely used in patients with non-small cell lung cancer, 43 breast cancer, 44 aggressive prolactinomas 45 and oesophageal cancers. 46 The nonconventional drugs predicted by the study may have a new use in choriocarcinoma.…”
Section: Discussionmentioning
confidence: 97%
“… 42 Lapatinib is widely used in patients with non-small cell lung cancer, 43 breast cancer, 44 aggressive prolactinomas 45 and oesophageal cancers. 46 The nonconventional drugs predicted by the study may have a new use in choriocarcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…[7,16] In a phase II study, the low accrual of eligible patients led to early discontinuation of the study, resulting in low-quality evidence. [19] Therefore, multinational and multicenter clinical trials are needed to achieve sufficiently powered studies. Furthermore, the included trials in this review were heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility and pathological response with lapatinib, a tyrosine kinase inhibitor of both HER2 and the epidermal growth factor receptor (EGFR), has been investigated in two phase II studies. [19,20] Overall, both studies showed safety of the addition of lapatinib to chemotherapy. Although Smyth et al demonstrated a significant increase in grade ≥3 diarrhea with the addition of lapatinib (24% vs 0%), postoperative complication rates were similar in both arms.…”
Section: Single Her2 Targeting With Tyrosine Kinase Inhibitorsmentioning
confidence: 91%
“…36 In a phase II study of lapatinib monotherapy in HER2-positive EAC, 12 patients (median age 64 years; 67% male) received a median of 5.6 weeks of treatment (range: 1.1-8.4), and among 4 out of 12 patients with tumor resection, one showed pathologic complete response; the remaining three showed pathologic partial response, which indicated that the treatment regimen was safe. 39 ECs with overexpression and amplification of HER2 are considered good candidates for HER2-targeted therapy, and the combination of trastuzumab and lapatinib is a new promising strategy for HER2-positive EC patients. 40,41 Trastuzumab emtansine (T-DM1) is an antibody-drug conjugate that combines the HER2-targeted properties of trastuzumab with the cytotoxic activity of emtansine, enabling selective delivery of chemotherapy to HER2-overexpressing cells.…”
Section: Her2-targeted Therapymentioning
confidence: 99%
“…Preplanned exploratory subgroup analyses showed that OS in the lapatinib arm was prolonged in Asian and younger patients 36 . In a phase II study of lapatinib monotherapy in HER2‐positive EAC, 12 patients (median age 64 years; 67% male) received a median of 5.6 weeks of treatment (range: 1.1–8.4), and among 4 out of 12 patients with tumor resection, one showed pathologic complete response; the remaining three showed pathologic partial response, which indicated that the treatment regimen was safe 39 . ECs with overexpression and amplification of HER2 are considered good candidates for HER2‐targeted therapy, and the combination of trastuzumab and lapatinib is a new promising strategy for HER2‐positive EC patients 40,41 …”
Section: Her2 and Ecmentioning
confidence: 99%